Breaking down silos: Conservation areas for Amazonian flagship terrestrial and freshwater species - Shahbol, Natalie; Arias, Melissa; Boron, Valeria; Wiederhecker, Helga Correa; Caldas De Oliveira, Bernardo; La Rosa, Fabiola; Naidoo, Robin; Oliveira‐Da‐Costa, Marcelo; Pacheco, Jessica; Frias, Mariana Paschoalini; Petrone, Sandra; Sainz, Lila; et al. (Society for Conservation Biology, 2025)
Research into the threats affecting flagship terrestrial and freshwater species in the Amazon has operated within disciplinary and ecological silos, neglecting the interconnectedness between these species and ecosystems. In this study, we aimed to bridge these divides by identifying Amazon areas harboring high jaguar densities and high richness of migratory freshwater species, highlighting the potential co‐benefits of integrated terrestrial and freshwater conservation approaches. We also assessed the risks posed to these areas by habitat and connectivity loss due to impending dam construction, deforestation, and the lack of coverage by area‐based conservation schemes. We found that 17% of the Amazon River Basin is covered by areas of high jaguar density and freshwater migratory species richness, 83% of which are found in Brazil and Peru. A third of these areas are located outside of formal protected areas or Indigenous territories, with Bolivia representing the largest gap in formal protection. The proposed construction of 54 hydroelectric dams and the expansion of deforestation poses an immediate threat to the habitats and connectivity of these areas. Given the risk of an Amazon ecological tipping point, our study underscores the need for integrated terrestrial and freshwater conservation approaches that set in motion international collaboration to secure transboundary flagship and umbrella species.